Drug Delivery: Superior Intratumoral Penetration of Paclitaxel Nanodots Strengthens Tumor Restriction and Metastasis Prevention (Small 21/2015). Issue 21 (June 2015) - Ni, Dezhi; Ding, Hui; Liu, Shan; Yue, Hua; Bao, Yali; Wang, Zhenhua; Su, Zhiguo; Wei, Wei; Ma, Guanghui
<x xml:space="preserve">Abstract</x> On page 2518, drug nanodots of ultra‐small sizes (around 10 nm) are prepared by W. Wei, G. Ma, and co‐workers. After decoration with iRGD ligands, these nanodots are demonstrated to possess superior ability in intratumoral infiltration over their counterparts with larger sizes (70 nm). Efficient cancer stem cell elimination and tumor growth/metastasis inhibition are thus achieved.